Design and experiment of high accuracy flowmeter for air duct - Qi, ZhongShuo (2018)
In HVAC system, air flow measurement is difficult to be measured accurately due to several factors such like air density is lower so that dynamic pressure is small and difficult to be measured. Besides, air turbulence and cross-sectional air velocity distribution in the larger diameter of air duct also contribute to inaccurate reading. Lastly, the space for installation of air flowmeter is limited in air duct which is hard to achieve fully developed velocity profile to meet the air flow measurement requirement. Because installation for flowmeter must be located at least 10 times diameter of air duct design. So, in order to achieve high accuracy flowmeter reading, laminar flow measurement is introduced and is one of the promising measurement methods for airflow rate. The reason is that current differential pressure sensor suffering from low sensitivity in air duct. This project aims to design Pressure-based laminar flow meter and force based laminar flow meter to improve accuracy of airflow rate. The flowmeter will be designed using mesh filter, force sensor (load cell) and transducer HX711. Experiments will be conducted in existing testing facilities which are consisted of air duct, centrifugal fan, orifice flowmeter, differential pressure sensor, electrical damper and National instrument board. Sample of data sets of flowmeter rate and pressure drop as well as flowmeter rate and force reading will be plotted using matlab program under different damper angle conditions. The deducible relationship from two phase experiment result which is approximately linear relationship. And quantitative analysis of the performance by analysing sample of data set will be done using Matlab. With the high sensitivity force sensor, airflow rate measurement accuracy will improve and the high pressure drop (suitable size of mesh openings) will be reduced to achieve better energy efficiency.